Formation mechanism and properties of twinned structures in (111) seeded directionally solidified solar grade silicon. (December 2016) - Oliveira, V.A.; Marie, B.; Cayron, C.; Marinova, M.; Tsoutsouva, M.G.; Sio, H.C.; Lafford, T.A.; Baruchel, J.; Audoit, G.; Grenier, A.; Tran Thi, T.N.; Camel, D.
Abstract: The growth structure of photovoltaic multicrystalline silicon formed by directional solidification presents a high fraction of Σ3 and higher order twins. Previous studies proposed that these complex structures are formed by a succession of 2D nucleation events of Σ3 twins on 111 growth facets at the triple line formed by their intersection with the crucible wall, another crystal, or the surface. In this work, we report the reproducible formation of multiple twinned domains inside solar grade Si single crystals grown by directional solidification above a (111) seed. These domains start on a Σ3 twin nucleated inside the crystal bulk, and systematically develop into similar twinned structures characterized by a ternary arrangement of grains in Σ3, Σ9, and Σ27 relationship. The mechanism of formation of the initial twin nucleus is discussed, and a scenario is proposed for the processes of subsequent multiple twinning. The growth competition between twin grains is shown to promote the appearance of incoherent twin boundaries, and dislocations near grain boundaries and in the twin grains themselves. The electrical activity of Σ-boundaries is measured, and the correlation between the structure of the defects and the resulting detrimental electrical activity is then discussed. Graphical abstract: